Enhancing Students’ Writing Achievement by Applying Sociogram: Vegi Sandika*, Marlita, Kurnia Febianti - Vegi Sandika; Marlita; Kurnia Febianti (Samudra Publisher, 2023)
Sociogram is a visual medium that illustrates the relationships and interactions that exist between characters and other characters. These visuals could assist students in writing stories more easily. The aims of this study are to describe and review Sociogram in enhancing students' writing achievement through a review of experts' opinions and the results of previous research on the definition and benefits of Sociogram. The findings of the study show that Sociogram were effective media and could enhance students' writing achievement regarding their motivation, literacy, creativity, and critical thinking. Sociogram also be used to develop students creativity in making stories, especially to support their writing. To write properly, students should improve their knowledge of vocabulary, grammar, and other components of writing. The sociogram is significant because it provides learners to understand the relationship between each character in a story, consider the primary character and their alignment with each other, and minor characters.